Evolutionary conserved NSL complex/BRD4 axis controls transcription activation via histone acetylation - Gaub, Aline; Sheikh, Bilal N.; Basilicata, M. Felicia; Vincent, Marie; Nizon, Mathilde; Colson, Cindy; Bird, Matthew J.; Bradner, James E.; Thevenon, Julien; Boutros, Michael; Akhtar, Asifa (Nature Communications, 2020)
Cells rely on a diverse repertoire of genes for maintaining homeostasis, but the transcriptional networks underlying their expression remain poorly understood. The MOF acetyltransferase-containing Non-Specific Lethal (NSL) complex is a broad transcription regulator. It is essential in Drosophila, and haploinsufficiency of the human KANSL1 subunit results in the Koolen-de Vries syndrome. Here, we perform a genome-wide RNAi screen and identify the BET protein BRD4 as an evolutionary conserved co-factor of the NSL complex. Using Drosophila and mouse embryonic stem cells, we characterise a recruitment hierarchy, where NSL-deposited histone acetylation enables BRD4 recruitment for transcription of constitutively active genes. Transcriptome analyses in Koolen-de Vries patient-derived fibroblasts reveals perturbations with a cellular homeostasis signature that are evoked by the NSL complex/BRD4 axis. We propose that BRD4 represents a conserved bridge between the NSL complex and transcription activation, and provide a new perspective in the understanding of their functions in healthy and diseased states.
Gesehen am 13.10.2020